2008
DOI: 10.2147/copd.s1758
|View full text |Cite
|
Sign up to set email alerts
|

Identifying targets for COPD treatment through gene expression analyses

Abstract: Despite the status of chronic obstructive pulmonary disease (COPD) as a major global health problem, no currently available therapies can limit COPD progression. Therefore, an urgent need exists for the development of new and effective treatments for COPD. An improved understanding in the molecular pathogenesis of COPD can potentially identify molecular targets to facilitate the development of new therapeutic modalities. Among the best approaches for understanding the molecular basis of COPD include gene expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 84 publications
0
10
0
Order By: Relevance
“…It is not clear how the p38 MAPK inhibitor suppressed smoke-induced changes leading to lung destruction. However, recent studies revealed that the p38 MAPK pathway regulates apoptosis, inflammation, and fibrosis, which are potentially associated with COPD pathogenesis [ 16 , 35 , 36 ]; 1) inflammatory neutrophil cell migration, 2) proinflammatory cytokine and chemokine release from inflammatory cells and airway smooth muscle, 3) release of degradative enzymes (eg, MMPs) and growth factors, 4) control of the production of interferon-γ from CD4 positive andCD8 positive T cells, and T-helper 1 differentiation of CD4 positive cells, 5) enhancement of bronchoconstrictor effects of airway smooth muscle associated with inflammation and oxidative stress, 6) airway remodeling, 7) induction of corticosteroid insensitivity. Moreover, inhaled CS stimulates epithelial cells and alveolar macrophages to release several chemotactic factors that attract inflammatory cells to the lungs, including neutrophils, T-helper 1 cells, type 1 cytotoxic T cells, and fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…It is not clear how the p38 MAPK inhibitor suppressed smoke-induced changes leading to lung destruction. However, recent studies revealed that the p38 MAPK pathway regulates apoptosis, inflammation, and fibrosis, which are potentially associated with COPD pathogenesis [ 16 , 35 , 36 ]; 1) inflammatory neutrophil cell migration, 2) proinflammatory cytokine and chemokine release from inflammatory cells and airway smooth muscle, 3) release of degradative enzymes (eg, MMPs) and growth factors, 4) control of the production of interferon-γ from CD4 positive andCD8 positive T cells, and T-helper 1 differentiation of CD4 positive cells, 5) enhancement of bronchoconstrictor effects of airway smooth muscle associated with inflammation and oxidative stress, 6) airway remodeling, 7) induction of corticosteroid insensitivity. Moreover, inhaled CS stimulates epithelial cells and alveolar macrophages to release several chemotactic factors that attract inflammatory cells to the lungs, including neutrophils, T-helper 1 cells, type 1 cytotoxic T cells, and fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the GWAS, there has been minimal overlap between the differentially expressed genes identified in each microarray study 18 ; greater overlap has been found for differentially expressed pathways. These microarray studies have been limited by variable definitions of COPD, incomplete consideration of past and current smoking status, failure to consider quantitative traits and COPD heterogeneity (such as emphysema and airway disease), and until recently, small sample sizes 19 20 . The COPD microarray studies have not found robust differential expression of the genes at GWAS loci, which has been shown in other complex diseases and traits, including coronary heart disease, height, type 2 diabetes, and autism 21 22 23 24 .…”
mentioning
confidence: 99%
“…By contrast, a study by Durham and Adcock (9) suggested that COPD is a driving factor in lung cancer. COPD is the leading cause of mortality projected to rank 3rd in 2020 (13) and comes under the environmental factors such as smoking (14). Exacerbation of COPD exhibits various symptoms that include cough, production of sputum or shortness of breath.…”
Section: Introductionmentioning
confidence: 99%
“…The key regulators or DEGs may be possible gene biomarker responsible for the disease condition (17,18). A few gene expression studies on COPD and lung cancer (14,15) are available; however, our aim is to identify DEGs and determine their functional analysis. The present study presents a systems biology perspective to decipher DEGs in lung cancer using microarray gene expression profiles and determine their functional analysis.…”
Section: Introductionmentioning
confidence: 99%